2017
DOI: 10.4236/ajps.2017.811194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NO<sub>2</sub> on Inflorescence Length, Pollen/Seed Amount and Phenolic Metabolites of Common Ragweed (<i>Ambrosia artemisiifolia</i> L.)

Abstract: Ambrosia artemisiifolia L. (common ragweed) is an annual ruderal plant that is native to Northern America but nowadays is also spreading across Europe, and its pollen is known to be highly allergenic. Air pollution, e.g. NOx and climate change may affect the plant growth, pollen production and duration of the entire pollen season. In this study, ragweed plants were grown over an entire vegetation period under 40 ppb NO 2 /clean air (control) and 80 ppb NO 2 (treatment). The inflorescence length was not affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We noted the concurrent rising of (1) birch pollen and NO 2 levels and (2) Bet v 1 allergen and CO levels over the MPS. Several researchers (e.g., Takahashi and Morikawa 2014 ; Zhao et al 2017 ) recognize nitrogen dioxide as an air pollutant that positively regulates the growth of vegetative and generative structures of plants, resulting in enhanced biomass and pollen production. On the other hand, carbon monoxide is associated with stress-related defense processes in plants, leading to enhanced allergenic protein content in pollen grains (Žiarovská et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We noted the concurrent rising of (1) birch pollen and NO 2 levels and (2) Bet v 1 allergen and CO levels over the MPS. Several researchers (e.g., Takahashi and Morikawa 2014 ; Zhao et al 2017 ) recognize nitrogen dioxide as an air pollutant that positively regulates the growth of vegetative and generative structures of plants, resulting in enhanced biomass and pollen production. On the other hand, carbon monoxide is associated with stress-related defense processes in plants, leading to enhanced allergenic protein content in pollen grains (Žiarovská et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Darbah et al ( 2008 ) studied the effect of elevated O 3 on Betula papyfera and reported higher production of catkins along with a decrease in catkin length, diameter, and mass. Studying Ambrosia artemisiifolia, Zhao et al ( 2017 ) found increased pollen and decreased seed production under elevated NO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased carbon dioxide (CO 2 ) concentrations have been reported to lead to an increase in pollen production (Ziska and Caulfield 2000 ; Jablonski et al 2002 ; Wayne et al 2002 ; Ziska et al 2003 ; Rogers et al 2006 ; Kim et al 2018 ). For air pollutants, nitrogen dioxide (NO 2 ) might reduce pollen production (Jochner et al 2013 ), but also the opposite has been documented (Zhao et al 2017 ). In addition, a study demonstrated that O 3 affects plant reproduction (Darbah et al 2008 ; Albertine et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This happens because plants exposed to higher levels of environmental stress tend to produce more defence-related allergenic proteins (Gilles et al 2018 ; Rauer et al 2021 ). It has been shown that these levels of stress also influence pollen production either positively (Zhao et al 2017 ) or negatively (Jochner et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%